Pelayanan Kepada Masyarakat Berbasis Pengetahuan Teknik Elektro dan Komputer di Desa Segoro Tambak, Kecamatan Sedati Kabupaten Sidoarjo, Propinsi Jawa Timur - R. Ahmad Cholilurrahman (Universitas Muhammadiyah Surabaya, 2018)
regency. The majority of the population are farmers. If viewed from the geographical situation, then this village is located near the Madura Sea. Where the weather conditions of Segoro Tambak village tend to be hot and dry, with access roads leading to the village quite easily even though the streets are still much damaged and dusty. The position of the village on a macro lane road to the direction of the Airport and City District and City Province. This condition gives an indication that the regional concession (sub-district) of Segorotambak Village has strategic function and role. While seen from the boundaries of the administrative area of Segorotambak Village are: North side: Tambakoso Village / Sungai Buntung, East: Madura Strait, South side: Banjar Kemuning Village and Juanda Airport, West: Pranti Village and Tambak Sawah Village. The problem is access to technology in this village is still lacking with the lack of facilities such as cafe, hotspot, place of printing and others. In addition, the majority of the villagers' education is only graduated from elementary school, where they prefer to work after graduating from primary school and do not continue to the higher level. This can be understood because the village of Segoro Tambak is a village where the daily livelihood of the population is to manage the fishponds, no wonder if their children are involved to help sustain the family economy with the majority of the population is farmers, the level of education also affect the lives of citizens , because hereditary have the same life with their parents, and very few who get higher education. In addition, if continuing higher education, more choose social sciences - humanities than the science of technology, whereas the development of the world of electronics in the sense of the development of information and communication technology is growing rapidly. As an evaluation, we lecturers from the Department of Electrical Engineering, FTI, ITATS held a community service activity as a form of dharma of three universities, packaged in real work college activities (KKN) - community empowerment learning (PPM) to Karang Taruna as the target audience community by holding